1994
DOI: 10.1007/bf03160080
|View full text |Cite
|
Sign up to set email alerts
|

mRNA levels of Ca2+-independent forms of protein kinase C in postischemic gerbil brain by Northern blot analysis

Abstract: To investigate the role of Ca(2+)-independent forms of protein kinase C (PKC) in ischemic neuronal injury, mRNA expression of PKC was studied by Northern blot analysis. Ischemia was produced in gerbils by 10-min bilateral carotid artery occlusion and was followed by recirculation for 15 min, 6 h, and 24 h. Brains of postischemic and sham-operated animals were removed, forebrains fresh frozen, and processed for Northern blot analysis. Three synthetic oligonucleotide probes based on published cDNA sequences of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…In the present study RT-PCR revealed that the mRNA for PKCa decreased while PKCz mRNA increased correspondingly with their respective protein levels. Changes in PKC mRNA in response to tissue injury has been demonstrated in response to an ischemic insult [39,40]. The corresponding changes in mRNA and protein expression for PKCa and PKCz suggest that these isoforms are transcriptionally-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study RT-PCR revealed that the mRNA for PKCa decreased while PKCz mRNA increased correspondingly with their respective protein levels. Changes in PKC mRNA in response to tissue injury has been demonstrated in response to an ischemic insult [39,40]. The corresponding changes in mRNA and protein expression for PKCa and PKCz suggest that these isoforms are transcriptionally-regulated.…”
Section: Discussionmentioning
confidence: 99%
“…26,48 Some reports demonstrate sustained activation of ⑀PKC after OGD 35,49 and, in response to kainic acid, a glutamate analog. 50 Other reports suggest that ⑀PKC is not activated in response to ischemia 51,52 in an in vivo model of spreading depression by cortical KCl application or by ischemic preconditioning. 31,53 ⑀PKC mRNA increases slightly at 1 hour after reperfusion; however, more significant upregulations were observed in the transcription of other PKC isozymes.…”
Section: Pkc Activity In Stroke Modelsmentioning
confidence: 99%
“…89,90 Studies demonstrate that ␦PKC is specifically upregulated and rapidly activated in response to reperfusioninduced intracellular signaling; in transient focal and global ischemia models, ␦PKC mRNA is upregulated within 24 hours after ischemia, as seen in perifocal cortex and in CA1 neurons, respectively. 51,91,92 Concomittantly, ␦PKC protein levels are increased in the perifocal region during reperfusion, 92 suggesting a role for this enzyme in mediating delayed-injury processes. Studies in an in vivo transient ischemia model show ␦PKC is rapidly activated at the onset of reperfusion, although this activity is not sustained at 24 hours after ischemia.…”
Section: Pkc␦ In Reperfusion Injury: Apoptosis Necrosis and Inflammmentioning
confidence: 99%
“…The CF-dPKC is a constitutively active enzyme, because it is freed from the autoinhibitory constraints imposed by theDelta protein kinase C has been implicated in mediating ischemic and reperfusion brain injuries. Delta protein kinase C mRNA increases after ischemia in CA1 neurons in gerbil and rat models of global ischemia (Savithiry and Kumar, 1994;Koponen et al, 2000). Delta protein kinase C mRNA and protein levels increase near an ischemic lesion after focal cerebral ischemia in rat (Miettinen et al, 1996).…”
Section: Introductionmentioning
confidence: 95%